Hyperbolic stress-strain parameters for non-linear Finite Element Analyses of stone column constructed in soft soil - K. T, Shlash (Iraqi Journal of Civil Engineering, 2005)
Abstracte: The stress-strain behavior of any type of soil depends on a number of different factors including density, water content, structure, drainage conditions, strain conditions (i.e., plane strain, triaxial), duration of loading, stress history, confining pressure, and shear stress. In many cases it may be possible to take account of these factors by selecting soil specimens and testing conditions which simulate the corresponding field condition. Even when this can be done accurately, however, it is commonly found that the soil behavior over a wide range of stresses is nonlinear, in elastic, and dependent upon the magnitude of the confining pressure employed in the tests. In order to perform stress analysis of soils, it is desirable to employ techniques, which account for these important aspects of soil behavior.